Studies on the chemical compositions and biological activities of essential oils of boesenbergia spp - Noorul Adawiyah, Mustahil (Universiti Malaysia Sarawak, UNIMAS, 2009)
The use of plants, plant extracts and plant-derived chemicals in the treatment of diseases, foods supplement and cosmetics is firmly rooted in the past and are still developing. Many drugs used in contemporary medicine have been derived from plants and were originally discovered through the traditional use by indigenous people.